Revision of Leinendera Carrera, 1945 (Diptera: Asilidae: Asilinae) with description of two new species - Camargo, Alexssandro; Vieira, Rodrigo; Rafael, José Albertino (Zootaxa, 2019)
Two new species of the Neotropical genus Leinendera Carrera, 1945, Leinendera carrerai sp. n. and Leinendera mnrj sp. n., and the female of Leinendera achaeta Camargo, Vieira, Köhler & Rafael, 2016 are described from Brazil. The habitus, wing, male terminalia and female terminalia for the latter species are described and illustrated. The female terminalia of Leinendera rubra Carrera, 1945 is also illustrated. An identification key for the five Leinendera species and a distribution map with new records are provided.